2017
DOI: 10.1590/1983-1447.2017.02.67712
|View full text |Cite
|
Sign up to set email alerts
|

Religiosidade prejudicada e sofrimento espiritual em pessoas vivendo com HIV/aids

Abstract: Objective: To verify the inference of Nursing Diagnoses, Impaired religiosity and Spiritual distress in people living with HIV/AIDS. Methods: This is a cross-sectional study with a quantitative approach, performed in a specialized Service CenteR of Recife, Pernambuco, from June to November 2015. The results related to 52 people living with HIV/AIDS and that were interviewed were analyzed by three nurse judges.Results: Spiritual distress was estimated at 73.1% (38), Impaired religiosity at 36.5% (19), with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
0
5
0
8
Order By: Relevance
“…The majority of these studies (29) were performed in healthcare contexts, especially with patients under treatment for chronic diseases such as: kidney failure (Valcanti et al 2012;Pilger 2015;Santos et al 2017), hepatitis C (Reis 2012), multiple sclerosis (Amoroso 2009), liver diseases (Martins et al 2012), epilepsy (Tedrus et al 2013); drug abuse (Correa 2016), cancer (Matos et al 2017;Gobatto 2012;Mesquita et al 2013;Borges 2015;Veit and de Castro 2013;Marucci 2012;Tarabay 2014) HIV AIDS (Faria and Seidl 2006;Pilger 2015;Pinhol et al 2017), and also among informal caregivers of elderly inpatients (Vitorino et al 2017). All of them highlight the more frequent use of positive than negative religious coping.…”
Section: Literature Review: Emprirical Studies On Spiritual/religiousmentioning
confidence: 99%
“…The majority of these studies (29) were performed in healthcare contexts, especially with patients under treatment for chronic diseases such as: kidney failure (Valcanti et al 2012;Pilger 2015;Santos et al 2017), hepatitis C (Reis 2012), multiple sclerosis (Amoroso 2009), liver diseases (Martins et al 2012), epilepsy (Tedrus et al 2013); drug abuse (Correa 2016), cancer (Matos et al 2017;Gobatto 2012;Mesquita et al 2013;Borges 2015;Veit and de Castro 2013;Marucci 2012;Tarabay 2014) HIV AIDS (Faria and Seidl 2006;Pilger 2015;Pinhol et al 2017), and also among informal caregivers of elderly inpatients (Vitorino et al 2017). All of them highlight the more frequent use of positive than negative religious coping.…”
Section: Literature Review: Emprirical Studies On Spiritual/religiousmentioning
confidence: 99%
“…The use of spiritual care in the context of care provides the patient with a reflection about the disease, as well as can assist in behavioral changes. [8,13] In the analysis of the power of determination of each domain on the total score, there is greater determination in the Psychological and Social Relations domains and less determination in Spirituality / Religiosity / Personal Beliefs. In planning care, it is important to consider that religiosity and spirituality can be used in the search for the meaning and reason for living in the context of illness and these strategies can contribute to the promotion of health and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…[14] In addition, it is of great relevance that the health professional has knowledge about religiosity and spirituality, since the use of these strategies can help in coping and accepting the disease, directly impacting adherence to treatment, consequently, improving clinical aspects and quality of life of PLHIV. [13] It is observed that there is no consensus regarding the mean of the domains presented by the WHO-QOL HIV-Bref QOL questionnaire. The results show better averages in the Social Relations, Spirituality and Environment domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The religiousness has been considered an important tool in the confrontation strategies of new situations that are imposed in the life of people living with HIV/Aids, enabling the individual to deal with these events with more confidence and reducing the stress and anxiety [23].…”
Section: Confrontation Of Religion and Religiousness On People With Aidsmentioning
confidence: 99%